Pretherapeutic Predictive Factors for Histological High‐Grade Parotid Gland Carcinoma. (10th July 2021) - Mikoshiba, Takuya; Ozawa, Hiroyuki; Watanabe, Yoshihiro; Kawaida, Miho; Sekimizu, Mariko; Saito, Shin; Yoshihama, Keisuke; Nakamura, Shintaro; Nagai, Ryoto; Imanishi, Yorihisa; Kameyama, Kaori; Ogawa, Kaoru
Abstract : Objective: The histological grade of parotid gland carcinoma (PGC) is an important prognostic factor; however, the diagnosis prior to treatment has been challenging to make. This study aimed to investigate whether the pretreatment clinical findings, including hematological inflammatory, nutritional, and immune markers, could predict the histological grade of PGC. Study Design: Retrospective study. Methods: We retrospectively enrolled 111 patients with PGC and evaluated the correlation between histological grade and pretreatment clinical findings such as age, sex, tumor staging, facial nerve paralysis, pain or tenderness, adhesion to the surrounding tissues or tumor immobility, and hematological markers. Results: Sixty patients (54%) were diagnosed with histological high‐grade PGC. Univariate analysis revealed that age, T classification, N classification, TNM stage, facial nerve paralysis, adhesion/immobility, C‐reactive protein (CRP), and CRP‐to‐albumin ratio (CAR) were significant predictors of PGC histological grade. On multivariate analysis, high T classification (T3, 4), high N classification (≥1), and elevated CRP (≥0.22 mg/dL) were independent predictors of high‐grade PGC. Conclusions: Pretreatment T classification, N classification, and CRP are significant predictors of the histological grading of PGC. Our results are useful for treatment planning and obtaining appropriate informed consent from the patients before treatment. Level of Evidence: 4 Laryngoscope, 132:96–102, 2022